Analysis of REM sleep without atonia in 22q11.2 deletion syndrome determined by domiciliary polysomnography: a cross sectional study. Issue 2 (28th December 2021) - Mauro, Jorge; Diaz, Mario; Córdova, Teresa; Villanueva, Katiuska; Cáceres, Tania; Bassi, Alejandro; Fritsch, Rosemarie; Repetto, Gabriela M; Ocampo-Garcés, Adrián
Abstract: Study Objectives: Our aim is to evaluate the presence of REM sleep without atonia (RWA), the objective hallmark of REM sleep Behaviour Disorder (RBD), as prodromal marker of Parkinson's disease (PD), in an adult cohort of 22q11.2 deletion syndrome (22qDS). Methods: Sleep quality was assessed by means of Pittsburgh quality scale index (PSQI), and RBD symptoms by means of RBD questionnaire-Hong-Kong (RBDQ-HK). Attended domiciliary video-Polysomnography (v-PSG) were performed in 26 adults (18–51 years, 14 females) 22qDS patients. Electromyogram during REM sleep was analyzed by means of SINBAR procedure at 3-second time resolution (miniepochs). Results: An overall poor sleep quality was observed in the cohort and high RBDQ-HK score in 7 of the 26 patients, two additional patients with positive dream enactment reported by close relatives had low score of RBDQ-HK. Nevertheless, SINBAR RWA scores were lower than cut-off threshold for RWA (mean 5.5%, range 0–12.2%). TST and the percentage of light sleep (N1) were increased, with preserved proportions of N2 and N3. Participants reported poor quality of sleep (mean PSQI > 5), with prolonged sleep latency in the v-PSG. No subjects exhibit evident dream enactment episodes during recording sessions. Conclusions: RWA was absent in the studied cohort of 22qDS adult volunteers according to validated polysomnographic criteria. High RBDQ-HK scores do not correlate with v-PSG results among 22qDS individuals.